IMPLEMENTASI NILAI-NILAI BERAGAMA DALAM KOMPONEN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM SEBAGAI UPAYA PEMBENTUKAN KARAKTER MODERAT DI SDN 096 TANJUNG JABUNG BARAT DAN SDN 106 TANJUNG JABUNG BARAT - Umar; Fitriyani Kosasih; Eliva Sukma Cipta (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the implementation of religious values within the components of Islamic Religious Education (IRE) learning as an effort to develop moderate character among students at SDN 096 Tanjung Jabung Barat and SDN 106 Tanjung Jabung Barat. The study was motivated by the importance of strengthening religious moderation from an early age through educational practices that integrate religious values into the learning process. A qualitative approach with a multisite study design was employed to obtain a comprehensive understanding of the implementation in both schools. The research participants consisted of principals, Islamic Religious Education teachers, classroom teachers, students, parents, and school committee members who were selected purposively. Data were collected through observations, in-depth interviews, and documentation, while data validity was ensured through source triangulation, technique triangulation, and member checking. Data analysis followed the interactive model of data condensation, data display, and conclusion drawing. The findings revealed that religious values had been integrated into all components of Islamic Religious Education learning, including learning objectives, instructional materials, teaching methods, learning media, and assessment practices. The implementation was further strengthened through teachers' role modeling, religious habituation programs, and a school culture that promoted discipline, honesty, tolerance, social responsibility, and mutual respect. Although several challenges were identified, such as differences in students' family backgrounds, limited instructional time, and the influence of digital media, both schools addressed these issues through collaboration among teachers, parents, and the wider school community. Therefore, integrating religious values into the components of Islamic Religious Education learning contributes significantly to the development of students' moderate character, enabling them to become religious, tolerant, responsible, and respectful individuals in a pluralistic society.